Insights into the electron-donating and withdrawing effect of the functional groups on mechanochemical dehydrochlorination reactions. Issue 29 (12th July 2017) - Guo, Fang; Wang, Zhen; Zhang, Jin-Jing; Famulari, Antonino; Li, Hai-tao; Martí-Rujas, Javier
Abstract : The effect on electron depletion in a partially fluorinated ligand has been evaluated in a dehydrochlorination reaction by converting outer sphere adducts into a coordination complex using experimental and DFT data. Abstract : The effect of the withdrawing ability of –CF3 groups in a large and flexible bidentate ligand has been evaluated by monitoring the course of solid-state dehydrochlorination reactions. We demonstrate that the coordination bond formation does not occur by mechanochemical means from a second coordination sphere adduct. Quantum mechanical calculations have shown that frontier molecular orbital energy and net charges at N centers can justify the less reactive nature of the partially fluorinated ligand, corroborating the experimental results.